O conselheiro do rei: a função de auditoria interna na governança corporativa de bancos no Brasil - Freitas, Volnei Adriano de (2015)
This study has as its theme the role of the Internal Audit Function (IAF) in the corporate governance system (CGS) in financial institutions, or simply banks, operating in Brazil. The FAI is an evaluation mechanism of procedures, policies and processes that acts from the operating environment of an organization. Based on this, the objective of this study was to investigate why and how the FAI was incorporated into the SGC and the consequences generated for both. The qualitative study, of exploratory and descriptive nature, used a multitheoretical approach, applying the agency theory and institutional theory. By this approach we tried to use the relationship between the need for monitoring to achieve organizational efficiency and the structural impact of the pressures of the external environment in defining the role and positioning of the FAI in the GSC. A semi-structured interview, used as data collection method, was applied to ten audit employees of five large banks, besides three people connected to the Board of Directors on banks. The study made the following findings: i) the FAI was incorporated into the SGC because the complexity derived from the evolution of the banking business made it difficult to monitoring banks by the principal and the regulator; ii) three factors worked in an interrelated way as drivers of this merger: the evolution of the banking business, the regulation and the convergence of assumptions and practices; and iii) the organizational repositioning resulted in consequences on the scope of the FAI work, the intensification of conflicts for the maintenance of independence, the perception of FAI value by CGS and the training process for internal auditors. The study had as main contributions to the CGS: the revelation of the potential of FAI to generate inputs to monitoring, by acting as its extension in the complex banking operating environment; and the proposed use of FAI as resources to generate inputs to strategic decisions. For FAI, the study suggests that, to be consolidated as governance mechanism, it needs to qualify its staff and develop methodologically to deliver consistent information to decision-making by GSC.